Responsibility in Transfer of Workers' Wages Limited Liability Company Bankruptcy - Abdullah, Ali; Jum Anggriani; Yongky Putut Angki Anata (Inovasi Pratama Internasional. Ltd, 2025)
The issue of responsibility in the transfer of workers' wages in a limited liability company that is bankrupt is an important issue in employment and bankruptcy law. When a limited liability company (PT) is declared bankrupt, there are significant challenges related to workers' rights, especially regarding unpaid wages. This study aims to analyze the legal responsibility in the transfer of workers' wage payment obligations from a bankrupt company to other parties, such as a third party or a replacement company. The methodology of this study uses a qualitative approach with case studies of several companies that are bankrupt. Data were collected through literature reviews, interviews with legal practitioners, and analysis of applicable laws and regulations. The findings of this study indicate that responsibility in the transfer of workers' wages depends not only on existing legal provisions, but also on the agreement between the parties involved in the bankruptcy process. The results of this study reveal that in practice, the transfer of responsibility for workers' wages often creates uncertainty for workers, especially in terms of certainty of payment. Recommendations provided include the need for clearer regulations regarding the transfer of wage obligations, as well as increasing legal protection for workers affected by company bankruptcy.